Подарок для самого слабого: сказка / В. Злотников ; худож. Р. Кобзарев - Злотников Виталий ("Сказки", 2014)
Экземпляры: ф.15 (20150320) / Инвентарный номер: 51467 / Цена: 20. 00. / Сис.шифр: Д / Авт.знак: З-68 / ГРНТИ: 17.82.93 / ББК: 84(2РОс=Рус)6